THE EFFECT OF MOTIVATION AND EMPLOYMENT ABILITY ON EMPLOYEE PERFORMANCE IN THE PAY-MENT OF MOTOR VEHICLE TAX SERVICES IN SAM-SAT, SUKABUMI CITY - Rizal Fauzi (Inovbiz: Jurnal Inovasi Bisnis, 2021)
This research was conducted at the Regional Revenue Management Center (PPPD) with a study on Motor Vehicle Tax Payment Services in the Samsat Sukabumi. The problem that occurs with the decrease in the number of motorcycle unit tax payments that do not re-register for tax payments in 2019, this occurs because the performance of employees is considered low and unable to achieve the set work targets, this is due to low levels of motivation and work ability. owned by employees, thus affecting the overall performance of employees. Respondents of the research were Samsat Sukabumi employees who were involved in the motor vehicle tax payment service as many as 31 people as the population, while the sampling technique used the saturated sampling method, because the number of samples was quite small, so that all populations were sampled. The instrument was tested with the reliability test and validity test, as well as the Classical Assumption Test. The research data were analyzed descriptively with Frequency and Associative tests with coefficient of determination, Correlation Analysis, Statistical Hypothesis Testing and Multiple Linear Regression Analysis. The results showed that: Employee Motivation (X1) and Work Ability (X2) had an influence on Employee Performance as indicated by the results of the coefficient of determination analysis of 49.5% while the remaining 50.5% was influenced by other factors not examined in this study.